Imaging the Deep Spinal Cord Microvascular Structure and Function with High‐Speed NIR‐II Fluorescence Microscopy. Issue 8 (22nd May 2022) - Zhang, Hequn; Zhu, Liang; Gao, Dave Schwinn; Liu, Yin; Zhang, Jun; Yan, Min; Qian, Jun; Xi, Wang
Abstract: The spinal cord (SC) is crucial for a myriad of somatosensory, autonomic signal processing, and transductions. Understanding the SC vascular structure and function thus plays an integral part in neuroscience and clinical research. However, the dense layers of myelinated ascending axons on the dorsal side inconveniently grant the SC tissue with high optical scattering property, which significantly hinders the imaging depth of the SC vasculature in vivo. Commonly used antiscattering techniques such as multiphoton fluorescence microscopy have low imaging speed and cannot capture the rapid vascular particle flow without significant motion blur. Here, advantage of the high penetration of near‐infrared (NIR)‐II fluorescence is taken to demonstrate a deep SC vascular structural image stack up to 350 µm, comparable to two‐photon microscopy. Furthermore, the red blood cells are labelled with the clinically approved NIR dye indocyanine. The combination of a fast NIR camera and indocyanine green‐red blood cells (RBCs) makes it possible to attain high‐speed 100 frame‐per‐second NIR‐II imaging to identify the corresponding changes in RBC velocity during the external hind leg stimulus. For the first time, it is established that the NIR‐II region would be a promising spectral window for SC imaging. NIR‐II fluorescence microscopy has excellent potential for clinical and basic science research on SC. Abstract : The imaging research on spinal cord (SC) vasculature is crucial, yet the high scattering tissue of SC greatly affects the improvement of microscopic imaging depth. Deep SC vascular structure is obtained, and fast monitoring of indocyanine‐green‐labeled red blood cells up to 100 fps is achieved by near‐infrared (NIR)‐II fluorescent microscopy, which exhibits the great potential of NIR‐II window on SC imaging.